Grammatical Errors of Google Translate in Translating Narrative Text in Indonesia to English - Br. Kembaren, Farida Repelita Waty; Daulay, Sholihatul Hamidah; Srikandi, Azura (Journal of English Teaching and Linguistics Studies (JET Li), 2023)
Many people have recently turned to machine translation to help them translate their documents. However, it is not widely used in the academic field, owing to worries about its trustworthiness in appropriately rendering the source text in the target language. This tool only translates on a word-by-word basis without considering the actual meaning of the text and grammar rules in English. It often applies to the Indonesian structure. So, when students are using Google Translate to translate a text, a new issue arises because it just transfers language without knowing the correct grammar. This research methodology is qualitative research with a content analysis method as the research design. From 5 narrative texts that have been translated by Google Translate from Indonesia to English found that there are two omission errors, four addition errors, six misinformation, and two misordering error and the most common error is misinformation. This study seeks to educate students about grammatical issues that can arise when using Google Translate, allowing them to avoid making the same mistakes and improve their knowledge.